Effects of thromboprophylaxis on mesenchymal stromal cells during osteogenic differentiation: an in-vitro study comparing enoxaparin with rivaroxaban. Issue 1 (December 2016) - Pilge, Hakan; Fröbel, Julia; Mrotzek, Silvia; Fischer, Johannes; Prodinger, Peter; Zilkens, Christoph; Bittersohl, Bernd; Krauspe, Rüdiger
Abstract Background Low-molecular-weight heparins (e.g. Enoxaparin) are widely used to prevent venous thromboembolism after orthopaedic surgery, but there are reports about serious side effects including reduction in bone density and strength. In recent years new oral antithrombotic drugs (e.g. direct Factor Xa-inhibitor, Rivaroxaban) have been used to prevent venous thromboembolism. However, there is lack of information on the effects of these new drugs on human mesenchymal stromal cells during osteogenic differentiation and, therefore, effects during postoperative bone healing. Methods We evaluated the effects of Rivaroxaban and Enoxaparin on the proliferation, mRNA and surface receptor expression as well as differentiation capacity of primary human mesenchymal stromal cells during their osteogenic differentiation. Results Enoxaparin, but not Rivaroxaban treatment significantly increased human mesenchymal stromal cell (hMSC) proliferation during the first week of osteogenic differentiation while suppressing osteogenic marker genes, surface receptor expression and calcification. Conclusions This is the first paper to demonstrate that Rivaroxaban had no significant influence on hMSC differentiation towards the osteogenic lineage, indicating a less affected bone healing process compared with Enoxaparin in vitro. Based on these findings Rivaroxaban seems to be superior to Enoxaparin in early stages of bone healing in vitro.